2017
DOI: 10.1136/bmj.j4197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of telephone first approach to demand management in English general practice: observational study

Abstract: Objective To evaluate a “telephone first” approach, in which all patients wanting to see a general practitioner (GP) are asked to speak to a GP on the phone before being given an appointment for a face to face consultation. Design Time series and cross sectional analysis of routine healthcare data, data from national surveys, and primary survey data. Participants 147 general practices adopting the telephone first approach compared with a 10% random sample of other practices in England. Intervention Management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 13 publications
4
93
0
Order By: Relevance
“…The literature highlights both positive and negative effects of telephone consultations on workload. 11,22,23 The present study enhances these findings by adding the trainees' points of view. Furthermore, although the study did not look specifically at patient satisfaction to telephone consultations, 24 positive patient feedback was rated highly as one of the reasons for positive experiences.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
See 1 more Smart Citation
“…The literature highlights both positive and negative effects of telephone consultations on workload. 11,22,23 The present study enhances these findings by adding the trainees' points of view. Furthermore, although the study did not look specifically at patient satisfaction to telephone consultations, 24 positive patient feedback was rated highly as one of the reasons for positive experiences.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
“…10 Telephone consultations may adversely affect patient safety, owing to less data gathering and rapport building than face-to-face consultations, and they may not reduce workload. 3,11 There is, therefore, a growing call for further professional development in delivering telephone consultations in order to improve quality and to guide changes in undergraduate and postgraduate training. 12 Greater understanding of the views and experiences of GPs is needed in training those responsible for shaping and delivering future primary care, particularly in terms of GPs' training needs, curricular requirements, and confidence in handling telephone consultations.…”
Section: Introductionmentioning
confidence: 99%
“…Using this classification, the articles reported that the telephone can be used as an additive, alternative or partially substitutive type of consultation 38,[43][44] . E-mail, on the other hand, has been used in an additive 16 or partially substitutive 16,20 consultation, especially for scheduling appointments, renewing prescriptions, solving doubts and to present test results 19 .…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Fact— The scope for telephone consultations is wide and includes prevention, hospital specialties, and surgical and psychiatric consultations56101112…”
Section: How Should I Conduct a Telephone Consultation?mentioning
confidence: 99%
“…Telephone consultations have the potential to improve access, convenience, and choice and are the most common alternative to face-to-face consultations 2. Comparative studies show that patient are equally satisfied with both forms of consultation 345. However, randomised controlled trials and time series studies show that telephone consultations do not necessarily reduce workload for clinicians 56…”
mentioning
confidence: 99%